(3GdhLjR aj efGRYGJ GdJfajP (B/s - (3eMahX, eMeO Cjef eMeOs ((3GdEScfOQjI, eUQ (B:s (3efTCI GdeYGQa,s, 2013)
(3jJfGhd GdeSJTGQ (B"(3eMeO Cjef eMahX(B" (3aj gPG GdcJGH (B"(3efGRYGJ GdJfajP(B" (3ajHjf dfG GNJUGU bGVj GdJfajP hTQhW GNJUGUg HfXQ efGRYGJ GdJfajP hjMOO eGgjI efGRYGJ GdJfajP GdehVhYjI hGdhbJjI heYjGQ GdJaQbI HjfgeG cPdc jHjf dfG GdfJGFL GdeJQJHI Ydi gPg GdJaQbI Hjf GdhbJjI hGdehVhYjI hjbOe dfG deMI aj bhGYO GdGNJUGU Gdbjej aj GdefGRYGJ GdehVhYjI cPdc aj ehGYjO GSJFfGa GdefGRYGJ GdhbJjI hGdehVhYjI(B. s
Keywords: (3JfajP GdCMcGes -- (3eUQs; (3JfajP GdCMcGe GdLfGFjIs -- (3eUQs